Advanced High Strength Steel Processing and Applications - Roy, Tapas Kumar; Bhattacharya, Basudev; Ghosh, Chiradeep; Ajmani, S. K. (Lecture Notes in Mechanical Engineering, 2018)
This volume comprises select proceedings of the AHSS 2017 conference. AHSS is an instrumental event in creating a platform for exchanging recent thoughts and results among a selective group of researchers working in the area of steel science and engineering. Twenty four papers selected papers have been included in this volume. This book will serve as a reference book to many practitioners and researchers working in the areas of steel strength, characterization, and applications. .